Skarga konstytucyjna w Hiszpanii – zarys historyczny oraz jej współczesny kształt - Gutierrez, Patryk (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
This paper deals with the institution of constitutional complaint in Spain with has been modified, and after 2007 is binding in it’s new legal form. The aim of this paper is to illustrate the differences and similarities, with were observed in the past before the year of 1978. The current form of constitutional complaint in Spain is discussed in the perspectives of the legal basis, material scope, and chosen procedure regulation.
Keywords: Spanish Constitution of 1978; rights and freedoms; Constitutional complaint; Protection of individual rights; Constitutional Court